An adsorption agent based on chitosan–zeolite composite: environmental and radioactive liquid waste remediation. Issue 3 (13th February 2023) - de Araujo, Leandro Goulart; Medeiros, Vinicius Litrenta; Guarnieri, Guilherme de Paula; da Silva, Danilo Antonio; Watanabe, Tamires; Marumo, Júlio Takehiro; Nery, José Geraldo
Abstract : Chitosan–zeolite composite as a low-cost and efficient material in the removal of caesium in synthetic and liquid organic radioactive waste solutions. Abstract : In this article, we present a chitosan–zeolite composite, which was synthesized and used as an adsorbent material for caesium (Cs) removal from aqueous media and real liquid radioactive organic waste (LROW). The compound was characterized by X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy techniques. The physicochemical characterization indicates the production of a composite. Adsorption experiments were first performed using the prepared solutions contaminated with Cs using full factorial design with two variables of interest: initial Cs concentration (Cs0 ) and adsorbent dosage (mg L −1 ). The results indicated a high caesium removal rate with removal values above 93% and adsorption capacity of up to 10 mg g −1 . With the best experimental conditions according to our experimental domain, time was evaluated and equilibrium was reached in 180 min. Finally, the adsorbent material was tested as an adsorbent for Cs, Am, and U from LROW. When in contact with LORW, the removal rates (%) were 21.51 ( 137 Cs), 26.39 ( 241 Am), and 20.26 (U (total)). Although lower, this material indicated that it has the potential to be used for multi-elemental adsorption.